2013
DOI: 10.4025/actasciagron.v35i3.21251
|View full text |Cite
|
Sign up to set email alerts
|

<b>GENES - a software package for analysis in experimental statistics and quantitative genetics</b> - doi: 10.4025/actasciagron.v35i3.21251

Abstract: ABSTRACT. GENES is a software package used for data analysis and processing with different biometric models and is essential in genetic studies applied to plant and animal breeding. It allows parameter estimation to analyze biological phenomena and is fundamental for the decision-making process and predictions of success and viability of selection strategies. The program can be downloaded from the Internet (http://www.ufv.br/dbg/genes/genes.htm or http://www.ufv.br/dbg/biodata.htm) and is available in Portugue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1,176
0
222

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,585 publications
(1,494 citation statements)
references
References 28 publications
2
1,176
0
222
Order By: Relevance
“…Regression models were chosen based on the significance of the model and coefficients, using Student's t-test (p≤0.05); also considering the coefficient of determination (R²). Data analysis was performed using the statistical software "GENES" (Cruz, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Regression models were chosen based on the significance of the model and coefficients, using Student's t-test (p≤0.05); also considering the coefficient of determination (R²). Data analysis was performed using the statistical software "GENES" (Cruz, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The method of Mojema using k = 1.25 (Cruz et al, 2013) indicated a cut at 80.37% of the genetic dissimilarity defining four groups. The first group gathers the cultivars with the initials B3; other group gathers the genotypes with the initials CS and UFV except UFVS2012; DM339 and MSOY6101 form another group, and the remaining group includes BARC-8 and BR8014887 which have high protein contents.…”
Section: Discussionmentioning
confidence: 99%
“…The combined analysis of variance was performed using the software Genes (Cruz, 2013) and the statistical model proposed in Equation 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agricultural research, in general, and in the genetic breeding area, in particular, many products have been generated within the scope of this motivation, both to implement techniques related to statistical methods and simulation, and to particularize or specialize these and other techniques (RESENDE, 2007;CRUZ, 2013;FERREIRA, 2013). From these initiatives and the aggregation of advanced computational techniques, the area of bioinformatics has emerged mainly related to the area of molecular biology, and more particularly, to applications in genomic selection and genome-wide selection (LEGARRA et al, 2009;GARRICK;SAATCHI, 2011).…”
Section: Introductionmentioning
confidence: 99%